Value of combined cross sectional and Doppler echocardiography in the detection of left ventricular pseudoaneurysm after mitral valve replacement. Issue 1 (July 1987) - Kupari, M; Verkkala, K; Maamies, T; Härtel, G
Abstract : The development of a left ventricular pseudoaneurysm is a rare complication of heart surgery. Until recently it has been impossible to detect without an angiographic study of the left ventricle. A combination of cross sectional and Doppler ultrasound studies led to the correct diagnosis in two patients with left ventricular pseudoaneurysms after mitral valve replacement. Cross sectional echocardiography showed a posterolateral echo-free space confined only by the pericardium and communicating with the left ventricle through a defect in the ventricular wall, and Doppler echocardiography confirmed the presence of blood flow in this cavity. This Doppler finding is critical if the perforation is too small to be identified reliably by cross sectional imaging. Surgical repair of the pseudoaneurysm can be undertaken without invasive studies if the echocardiographic findings are unequivocal and there is no reason to suspect the integrity of the circumflex coronary artery.